Approximate dynamic programming for the military inventory routing problem - McKenna, Rebekah S.; Robbins, Matthew J.; Lunday, Brian J.; McCormack, Ian M. (Annals of operations research, 2020)
The United States Army can benefit from effectively utilizing cargo unmanned aerial vehicles (CUAVs) to perform resupply operations in combat environments to reduce the use of manned (ground and aerial) resupply that incurs risk to personnel. We formulate a Markov decision process (MDP) model of an inventory routing problem (IRP) with vehicle loss and direct delivery, which we label the military IRP (MILIRP). The objective of the MILIRP is to determine CUAV dispatching and routing policies for the resupply of geographically dispersed units operating in an austere, combat environment. The large size of the problem instance motivating this research renders dynamic programming algorithms inappropriate, so we utilize approximate dynamic programming (ADP) methods to attain improved policies (relative to a benchmark policy) via an approximate policy iteration algorithmic strategy utilizing least squares temporal differencing for policy evaluation. We examine a representative problem instance motivated by resupply operations experienced by the United States Army in Afghanistan both to demonstrate the applicability of our MDP model and to examine the efficacy of our proposed ADP solution methodology. A designed computational experiment enables the examination of selected problem features and algorithmic features vis-à-vis the quality of solutions attained by our ADP policies. Results indicate that a 4-crew, 8-CUAV unit is able to resupply 57% of the demand from an 800-person organization over a 3-month time horizon when using the ADP policy, a notable improvement over the 18% attained using a benchmark policy. Such results inform the development of procedures governing the design, development, and utilization of CUAV assets for the resupply of dispersed ground combat forces.